(3x²-2x+9)-(3x-1)(x+4)
Soluções para a tarefa
Respondido por
12
(3x² - 2x + 9) - (3x - 1) . ( x + 4)
(3x² - 2x + 9) - (3x . x + 3x . 4 - 1 . x - 1 . 4)
3x² - 2x + 9 - (3x² + 12x - x - 4)
3x² - 2x + 9 - (3x² + 11x - 4)
3x² - 2x + 9 - 3x² - 11x + 4
= -13x + 13 => resposta
= -13.(x - 1) => resposta simplificada
(3x² - 2x + 9) - (3x . x + 3x . 4 - 1 . x - 1 . 4)
3x² - 2x + 9 - (3x² + 12x - x - 4)
3x² - 2x + 9 - (3x² + 11x - 4)
3x² - 2x + 9 - 3x² - 11x + 4
= -13x + 13 => resposta
= -13.(x - 1) => resposta simplificada
Perguntas interessantes
História,
1 ano atrás
Inglês,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Informática,
1 ano atrás
Matemática,
1 ano atrás